2020
DOI: 10.2196/18223
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision Making and Patient-Centered Care in Israel, Jordan, and the United States: Exploratory and Comparative Survey Study of Physician Perceptions

Abstract: Background Shared decision making (SDM) is a health communication model that evolved in Europe and North America and largely reflects the values and medical practices dominant in these areas. Objective This study aims to understand the beliefs, perceptions, and practices related to SDM and patient-centered care (PCC) of physicians in Israel, Jordan, and the United States. Methods A hypothesis-generating comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
(44 reference statements)
1
14
0
Order By: Relevance
“…A study by Zisman-Ilani et. al, revealed several issues related to the patient-physician relationship such as lack of time and training, the role of insurance companies, the incentive structure, and lack of support for physicians [ 14 ]. Another study investigating the barriers to communication between family physicians and patients in Dubai showed that female patients experience more time limitations during consultation where not all their issues are addressed as compared to their male counterparts [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Zisman-Ilani et. al, revealed several issues related to the patient-physician relationship such as lack of time and training, the role of insurance companies, the incentive structure, and lack of support for physicians [ 14 ]. Another study investigating the barriers to communication between family physicians and patients in Dubai showed that female patients experience more time limitations during consultation where not all their issues are addressed as compared to their male counterparts [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recommendations are also strongly biased toward Western countries and culture, as well as being White or belonging to a majority group. [58][59][60][61] Considering the international impact of NICE guidelines on SDM practice, and since many studies of SDM in mental health fall outside of the NICE inclusion criteria, we worry that this narrow representation of SDM will become the gold standard, overlooking other effective research and interventions of SDM in mental health. For example, the NICE guidelines ignore the concept of shared advance decision making in mental health, SDM around decisions about advance care planning 62,63 and the significant body of literature in mental health around the Joint Crisis Plan.…”
Section: Bias In Addressing Cultural Differences In Sdm Practicementioning
confidence: 99%
“… 81 Nearly half of the studies included originated either from Canada or the United States, which is significant as Canada and the United States are the world’s leading researchers of SDM. 82 To bring this into perspective, Ottawa Hospital Research Institute in Canada ( www.decisionaid.ohri.ca/index.html ), EBSCO information services in the United States ( www.ebsco.com/ ), and Mayo Clinic SDM National Resource Centre ( www.shareddecisions.mayoclinic.org/ ) all established websites related to PDAs, which have been widely spread all over the world.…”
Section: Discussionmentioning
confidence: 99%